Quorum-sensing signal binding results in dimerization of TraR and its release from membranes into the cytoplasm - Qin, Yinping (Oxford University Press, 2000)
Promoter binding by TraR and LuxR, the activators of two bacterial quorum-sensing systems, requires their cognate acyl-homoserine lactone (acyl-HSL) signals, but the role the signal plays in activating these transcription factors is not known. Soluble active TraR, when purified from cells grown with the acyl-HSL, contained bound signal and was solely in dimer form. However, genetic and cross-linking studies showed that TraR is almost exclusively in monomer form in cells grown without signal. Adding signal resulted in dimerization of the protein in a concentration-dependent manner. In the absence of signal, monomer TraR localized to the inner membrane while growth with the acyl-HSL resulted in the appearance of dimer TraR in the cytoplasmic compartment. Affinity chromatography indicated that the N-terminus of TraR from cells grown without signal is hidden. Analysis of heterodimers formed between TraR and its deletion mutants localized the dimerization domain to a region between residues 49 and 156. We conclude that binding signal drives dimerization of TraR and its release from membranes into the cytoplasm.